Socioecological benefits of academic greenspace for human health, plant, and pollinator diversity: A mixed-method study protocol - Temitope Kehinde; Adesanmi Akinsulore; Boladale O. Mapayi; Victor Okorie; Matthew Oziegbe; Charlotte Ndiribe; Opeyemi Adedoja; Ibukun Balogun (PLoS ONE, 2025)
Introduction Significant risks to the health of humans and ecosystems are posed by environmental pollution, urban warming, and fragmentation, which are primary urban factors that contribute to the deterioration of urban ecosystems. The purpose of this multidisciplinary study is to compare greenspaces in university campuses and the host cities in order to assess how valuable they are for promoting human and ecosystem health in Nigeria. Methods Mixed-methods research that will be conducted in five tertiary institutions and their host cities in southwestern Nigeria. Based on the objectives, the study is divided into four work packages (WP). WP 1 will use suitable sampling traps and scheduled field observations to quantify the diversity of plants and pollinators. Quantitative evaluation of well-being and mental health will be done in WP 2. In WP 3, the relationship between ecosystem health and mental health will be examined and in-depth interviews will be used to explore the socioecological perceptions and interaction of people with specific indicators of ecosystem health in greenspace. In WP 4, a nature-based intervention will be developed and evaluated in a pilot study to determine its feasibility and acceptability. Results The 2023 TETFund National Research Fund Intervention provided funding for this work, which is currently ongoing and results are not yet available. Conclusion This project will provide scientific knowledge to support evidence-based policy for relevant stakeholders and regulatory organisations, with the goal of promoting greenspace infrastructure in Nigerian tertiary institutions. This article is focused on describing the research design, as the study is currently on-going hence, there is no conclusion yet.